Malignant Glomus Tumor (Glomangiosarcoma) of Intestinal Ileum: A Rare Case Report - Ahmed Abu-Zaid; Ayman Azzam; Tarek Amin; Shamayel Mohammed (Hindawi Limited, 2013)
Glomus tumors are rare mesenchymal neoplastic lesions arising from glomus bodies that are involved in skin thermoregulation. They are mostly benign tumors, and malignant variants have been rarely reported. The subungual zones of fingers and toes are the most frequent sites of observation. Glomus tumors arising in visceral organs of the gastrointestinal tract are exceedingly rare. Stomach antrum and intestinal duodenum are the most frequent organs involved. No single case of glomus tumor involving intestinal ileum has been previously reported in the English medical literature. To the best of our knowledge, we report the first case of malignant glomus tumor (glomangiosarcoma) of intestinal ileum in a 29-year-old female patient who presented with a 1-month history of a tender pelvi-abdominal mass, constipation, vomiting, and melena. The intestinal ileum glomus tumor was resected, and histopathological diagnosis was consistent with glomangiosarcoma. A postoperative 6-month followup failed to show any evidence of tumor recurrence.